Women of the great barrier reef: Stories of gender and conservation - Foxwell-Norton, Kerrie; Anderson, Deb; Leitch, Anne M. (Queensland Review, 2021)
In the late 1970s, Carden Wallace was at the beginning of her lifelong exploration of the Great Barrier Reef - and indeed, reefs all over the world. For Wallace, who is now Emeritus Principal Scientist at Queensland Museum, the beginning of her Reef career coincided with the emergence of both feminist and environmental movements that meant her personal and professional lives would be entwined with a changing social, cultural and political milieu. In this article, we couple the story of Wallace's personal life and her arrival in coral science to identify the Reef as a gendered space ripe to explore both feminist and conservation politics. The article is part of a broader Women of the Reef project that supports a history of women's contribution to the care and conservation of the Reef since the 1960s. In amplifying the role of women in the story of the Reef, we find hope in the richness of detail offered by oral history to illuminate the ways discourse on the Reef and its women sits at the intersection of biography, culture, politics and place. In these stories, we recognise women's participation and leadership as critical to past challenges, and to current and future climate change action. By retelling modern Reef history through the experiences and achievements of women, we can develop new understandings of the Reef that disrupt the existing dominance of patriarchal and Western systems of knowledge and power that have led us to the brink of ecological collapse. © The Author(s), 2022.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; approches et analyses; australie; changements climatiques; environnement; histoire et politique; océanie; patriarcat; projet charge mentale; périodes historiques; régions géographiques; rôle des femmes dans la protection de la grande barrière de corail; systèmes d'oppressions; thématiques

Écoresponsabilité : la nouvelle « charge morale » des femmes - Lemelin, Silvie (2020)
Apparu dans les années 1980, le concept de charge mentale a été popularisé et brillamment illustré par Emma dans sa désormais célèbre bande dessinée Fallait demander [1]. La charge mentale, c’est la charge cognitive invisible que représentent la planification, l’organisation et la gestion de tout ce qui se situe dans la sphère domestique (tâches ménagères, rendez-vous, achats, soins aux enfants, etc.) et qui, chez les couples hétérosexuels[2], échoit généralement aux femmes en plus de leur activité professionnelle. Car les hommes, consciemment ou pas, désignent souvent leur compagne comme la responsable en titre de la logistique familiale. Et ce travail invisible prend énormément de temps et d’énergie psychique ; il génère davantage de stress que l’accomplissement des tâches domestiques comme telles, la charge mentale accompagnant les femmes au boulot et dans toutes leurs activités.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; approches et analyses; care; charge mentale; environnement; hétérosexisme; inégalités; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail invisible

Les femmes, l’environnement et le développement durable - Braidotti, Rosi; Charkiewicz, Ewa; Häusler, Sabine; Wieringa, Saskia (Genre, mouvements populaires urbains et environnement, 2007)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; discours dominant; environnement; histoire et politique; inégalités; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; systèmes d'oppressions; thématiques; écoféminisme